Implementation of Virtual Laboratory-Based Interactive Learning Media for Students' Science Literacy Skills on Temperature and Heat Material - Perlis Tantalama; Tirtawaty Abdjul; Nurhayati Nurhayati; Abdul Haris Odja; Mohammad Yusuf (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The low scientific literacy of students in Indonesia is caused by the monotonous learning process that makes students bored with learning. This study aims to determine the effect of a virtual laboratory based on PhET simulation on students' scientific literacy in temperature and heat. This study used a quasi-experimental, non-equivalent control-group design with two experimental and two control classes of seventh-grade students during the 2025/2026 academic year. Data were collected using pre-test and post-test scientific literacy instruments. The results of the independent-samples t-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant effect of the virtual laboratory on students' scientific literacy. In addition, the N-Gain analysis showed that the control class was in the low category (0.17 and 0.14), while the experimental class was in the medium category (0.63). The uniqueness of this study lies in integrating a virtual laboratory based on PhET simulations with scientific literacy indicators in teaching temperature and heat. These findings indicate that virtual laboratory media can effectively improve students' scientific literacy. PhET simulation-based virtual laboratories can serve as an effective technology-enhanced learning tool to improve students' scientific literacy, particularly in understanding temperature and heat concepts in junior high school science education.